2019
DOI: 10.1371/journal.pone.0219501
|View full text |Cite
|
Sign up to set email alerts
|

Comparing low-cost handheld autorefractors: A practical approach to measuring refraction in low-resource settings

Abstract: PurposeTo compare and validate the accuracy and ease of use of handheld autorefractors against retinoscopic refraction by an ophthalmologist for assessing the visual acuity of older adults in India.Methods190 patients were enrolled at the Sankara Eye Hospital in Bangalore, India, to undergo refraction using three different handheld devices—Retinomax (Nikon Inc., Japan), Netra (Eyenetra, Inc., USA), and QuickSee (PlenOptika, Inc., USA)—and the results were compared with cycloplegic retinoscopy and refraction do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 8 publications
1
20
0
Order By: Relevance
“…In addition, the device is portable, handheld and easy to use and more affordable than J o u r n a l P r e -p r o o f traditional autorefractors currently on the market, making it particularly attractive in low resource settings. Our findings are consistent with previous research where other autorefractors have shown high concordance with SR (15,(19)(20)(21)24). Authors have also reported that patients are happy with eyeglasses prescribed using autorefraction in various settings (13,20,25,26).…”
Section: J O U R N a L P R E -P R O O F Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In addition, the device is portable, handheld and easy to use and more affordable than J o u r n a l P r e -p r o o f traditional autorefractors currently on the market, making it particularly attractive in low resource settings. Our findings are consistent with previous research where other autorefractors have shown high concordance with SR (15,(19)(20)(21)24). Authors have also reported that patients are happy with eyeglasses prescribed using autorefraction in various settings (13,20,25,26).…”
Section: J O U R N a L P R E -P R O O F Discussionsupporting
confidence: 92%
“…QuickSee (PlenOptika Inc, Boston, MA, USA) is a portable autorefractor marketed at relatively low cost compared to existing devices. The accuracy of this device has already been established in both high-and low-resource settings (19)(20)(21). The aim of the current randomized clinical trial was to compare patient acceptance of eyeglasses with prescriptions based on autorefractions derived from this to those derived from the current standard, subjective refraction.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…Recent clinical studies of QuickSee have focused on comparing the agreement of the device with SR in several adult populations. While it was found that QuickSee provided excellent agreement with SR in those groups [ 14 , 15 , 17 , 18 ], the performance of the device in children, a significantly more challenging population, remained unknown. This work presents the first evaluation of the performance of this binocular wavefront autorefractor in characterizing refractive errors in pediatric populations.…”
Section: Introductionmentioning
confidence: 99%
“…These goals aspire to be met with as cost-effectiveness of a product as possible, as portable of a device design as possible, and with as minimal human resource expertise and training as possible for operating the equipment. 35 , 36 The three autorefractor evaluated in this study meet most of these criteria (see Table 1 ). The design elements of any measurement technique are attractive only if accurate and repeatable measurements are obtained using that technique.…”
Section: Discussionmentioning
confidence: 99%